Usability engineering study in the European Union of a redesigned follitropin alfa pen injector for infertility treatment. (1st September 2016) - Jeannerot, Fabien; Stüdeli, Thomas; Gunther-LaVergne, Lisa; Hirning, David; Schertz, Joan
ABSTRACT: Objectives : The prefilled, multidose, GONAL-f  ® (follitropin alfa) pen injector was redesigned to improve ease of use and pen functionality. This usability engineering evaluation aimed to demonstrate that the redesigned pen injector could be used by the intended users to safely and effectively deliver follitropin alfa. Methods : Formative and summative usability engineering evaluations of the pen injector, training and instructions for use (IFU) were conducted. This included an expert review, and formative and summative evaluations involving patients with infertility and fertility nurses. For the summative evaluation, participants received training and subsequently performed tasks based on three selected hazard-related use scenarios to evaluate real-world use, including simulated injections. Results : The formative evaluations confirmed that the pen injector was ready for summative evaluation. Task performance was high in the summative evaluation for both patients and nurses; the tasks that were observed to be most difficult to complete were priming the pen, completing an incomplete injection and completing the treatment diary. Participants rated the device as having above average usability. Most patients ranked the overall system (pen injector, device training and IFU) and its individual components to be either 'extremely easy' or 'somewhat easy' to use. Conclusions : These usability engineering evaluations demonstrated that patients and nurses could safely and effectively use the redesigned GONAL-f pen injector, and that they also found the IFU and device training to be easy to use.